PREVALENCE AND IMPACT OF SEXUAL VIOLENCE ON ADOLESCENTS IN MOJOKERTO DISTRICT - Noer Saudah; Indah Lestari; Chasiru Zainal Abidin (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Sexual violence is a serious issue in maternity nursing as it directly impacts reproductive health, including physical trauma, damage to reproductive organs, unwanted pregnancies, and prolonged psychological trauma. This study aimed to measure the prevalence of sexual violence among adolescents in Mojokerto Regency and describe its forms and impacts. The research employed a descriptive design, conducted in Mojokerto Regency from July to September 2025. A total of 220 respondents were selected using accidental sampling. The study variables included the prevalence of sexual violence incidents and their impacts, measured using a questionnaire. Data were analyzed using frequency distribution. The results showed that 118 adolescents (53.7%) had experienced sexual violence. The most common type was verbal harassment (40.7%), followed by a combination of verbal and physical violence (29.6%), physical violence (17%), and chat calling (12.7%). The most significant impact experienced by victims was social (44.8%), followed by combined physical-psychological-social impacts (22.7%), psychological (12.7%), spiritual (8.4%), physical (7.2%), and physical-psychological (4.2%). The dominance of female victims reflects the influence of patriarchal culture and gender inequality. The prevalence of verbal violence indicates low public awareness that certain utterances constitute harassment. Sexual violence often leads to social isolation, necessitating holistic management to enable adolescents to recover in a safe and supportive environment.